2017
DOI: 10.1177/1035304617717130
|View full text |Cite
|
Sign up to set email alerts
|

Why do economists study happiness?

Abstract: Recently economists have expressed increasing interest in studying the determinants of happiness. Their main task has been to identify economic and non-economic sources of well-being to define policies aimed at maximising happiness in nations. As yet, it has not been precisely explained why ‘happiness economics’ is actually a part of economic science. In this article, we show that happiness can be an economic concept providing a critical review of the literature on (a) economic applications of happiness data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 98 publications
1
23
0
1
Order By: Relevance
“…The studies of Helliwell, Layard, Stiglitz et al, Veenhoven, Diener and Seligman and others [ 8 – 12 ], have shown beyond a shadow of a doubt that if policymakers want to maximise the quality of life of their citizens, they need to consider subjective measures of well-being. Piekalkiewicz [ 13 ] states that happiness may act as a determinant of economic outcomes: it increases productivity, predicts one's future income and affects labour market performance. By measuring happiness, individuals themselves reveal their preference and assigned priority to various domains, which cannot be identified by a measure such as GDP.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The studies of Helliwell, Layard, Stiglitz et al, Veenhoven, Diener and Seligman and others [ 8 – 12 ], have shown beyond a shadow of a doubt that if policymakers want to maximise the quality of life of their citizens, they need to consider subjective measures of well-being. Piekalkiewicz [ 13 ] states that happiness may act as a determinant of economic outcomes: it increases productivity, predicts one's future income and affects labour market performance. By measuring happiness, individuals themselves reveal their preference and assigned priority to various domains, which cannot be identified by a measure such as GDP.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Bryson et al . (2016) and Piekalkiewicz (2017) state that happiness may act as a determinant of economic outcomes: it increases productivity, predicts one’s future income and affects labour market performance. Many constitutions state that maximising happiness is at the core of their policymaking.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is much less research on the effects of heat stress 1 more broadly on well-being [subjective wellbeing (SWB)], of which physical health is one facet. Variations in well-being have economic consequences (Piekałkiewicz 2017) and hot weather reduces wellbeing even if the effects are not physically manifest (Rehdanz and Maddison 2005;Connolly 2013;Tsutsui 2013). However, the concept of well-being has many dimensions (Steptoe et al 2015;Frey 2018).…”
Section: Introductionmentioning
confidence: 99%